Differences in SARS-CoV-2-Specific Antibody Responses After the First, Second, and Third Doses of BNT162b2 in Naïve and Previously Infected Individuals: A 1-Year Observational Study in Healthcare Professionals - Ogrič, Manca; Žigon, Polona; Podovšovnik, Eva; Lakota, Katja; Sodin-Semrl, Snezna; Rotar, Žiga; Čučnik, Saša (Frontiers in Immunology, 2022)
Background Safe and effective vaccines against COVID-19 are critical for preventing the spread of SARS-CoV-2, but little is known about the humoral immune response more than 9 months after vaccination. We aimed to assess the humoral immune response after the first, second, and third (booster) doses of BNT162b2 vaccine in SARS-CoV-2 naïve and previously infected healthcare professionals (HCP) and the humoral immune response after infection in vaccinated HCP. Methods We measured anti-spike (anti-S) and anti-nucleocapsid antibodies at different time points up to 12 months in the sera of 300 HCP who had received two or three doses of BNT162b2 vaccine. Mixed-model analyses were used to assess anti-S antibody dynamics and to determine their predictors (age, sex, BMI, and previous infection). Results Naïve individuals had statistically lower anti-S antibody concentrations after the first dose (median 253 BAU/ml) than previously infected individuals (median 3648 BAU/ml). After the second dose, anti-S antibody concentrations increased in naïve individuals (median 3216 BAU/ml), whereas the second dose did not significantly increase concentrations in previously infected individuals (median 4503 BAU/ml). The third dose resulted in an additional increase in concentrations (median 4844 BAU/ml in naïve and median 5845 BAU/ml in previously infected individuals). Anti-S antibody concentrations steadily decreased after the second dose and after the third dose in naïve and previously infected individuals. In addition, we found that age had an effect on the humoral immune response. Younger individuals had higher anti-S antibody concentrations after the first and second doses. After infection with the new variant Omicron, a further increase in anti-S antibody concentrations to a median value of 4794 BAU/ml was observed in three times vaccinated HCP whose anti-S antibody concentrations were relatively high before infection (median 2141 BAU/ml). Our study also showed that individuals with systemic adverse events achieved higher anti-S antibody concentrations. Conclusion In this study, significant differences in humoral immune responses to BNT162b2 vaccine were observed between naïve and previously infected individuals, with age playing an important role, suggesting that a modified vaccination schedule should be practiced in previously infected individuals. In addition, we showed that the high anti-S antibodies were not protective against new variants of SARS-CoV-2.